Particle technology and engineering : an engineer's guide to particles and powders: fundamentals and computational approaches - Seville, J. P. K. (Jonathan P. K.); Wu, Chuan-Yu (Professor of chemical engineering) (Butterworth-Heinemann/IChemE series., 2016)
This guide presents the basic knowledge and fundamental concepts that are needed by engineers dealing with particles and powders.